Estimated glucose disposal rate and markers of liver injury - Xin Tang; Xiaohan Ma; Tong Wu; Peiling Zuo; Sheng Chen; Xiaofei Zhang; Encun Hou (Medicine, 2026)
To estimate the glucose disposal rate (eGDR) as a newly validated surrogate marker of insulin resistance, this study examines its association with liver dysfunction, a relationship seldom explored. Accordingly, this research aims to investigate potential correlations between eGDR and markers of liver injury. This analysis utilized data from the National Health and Nutrition Examination Survey spanning 2005 to 2018. Multiple linear regression models were employed to assess the association between eGDR and markers of liver injury. Secondary analyses included subgroup evaluations and restricted cubic spline modeling. In the fully adjusted model, eGDR demonstrated a significant negative association with alanine aminotransferase (ALT) (β = −2.25, 95% CI: −2.66 to −1.84, P < .0001), aspartate aminotransferase (AST) (β = −0.66, 95% CI: −0.90 to −0.42, P < .0001), alkaline phosphatase (ALP) (β = −2.55, 95% CI: −2.96 to −2.13, P < .0001), and gamma-glutamyl transferase (GGT) (β = −2.85, 95% CI: −3.33 to −2.37, P < .0001). A nonlinear negative correlation was identified between eGDR and markers of liver injury ( P for nonlinearity < .05). In each subgroup, eGDR was not correlated with ALT in non-Hispanic Black, hypertensive patients, and diabetes mellitus (DM) patients, but showed a significant negative correlation in all other subgroups (all P < .05). Interaction tests revealed significant differences in the correlation between eGDR and ALT across age, ethnicity, body mass index (BMI), cancer presence, and hypertension strata ( P for interaction < .05). Similarly, eGDR’s correlation with AST varied significantly across strata of age, ethnicity and hypertension ( P for interaction < .05). Furthermore, the correlation between eGDR and ALP) showed significant variation across age, sex, BMI, and hypertension strata ( P for interaction < .05). Finally, eGDR’s correlation with GGT varied significantly across age, ethnicity, BMI, hypertension, and DM strata ( P for interaction < .05). This cross-sectional study identified a negative association between eGDR and markers of liver injury.